FASILITAS DI OBJEK WISATA NGALAU INDAH KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Edward, Fandy; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In research using this descriptive qualitative research method, there is a purpose to know the description of facilities in Tourism Object Ngalau Indah Payakumbuh West Sumatra Province. In addition, this research is also trying to know the management of facilities in Tourism Object Ngalau Indah Payakumbuh. Based on the results of research that has been done there are results indicating that the facilities in Tourism Object Ngalau Indah still has the shortcomings and not the maximum management of facilities in the beautiful tourist attraction. Viewed from the main facility only toilet facilities and facilities where the photo facilities available in Ngalau Indah Tourism Object is quite good only hygiene and treatment is less than the maximum seen from the Main Facility only toilet and photo place is still clean and well maintained because the building is still new and good. Apart from these 2 facilities the average cleanliness and perwatannya less than the maximum. Judging from the supporting facilities available in this beautiful tourist attraction such as mushalla less good because it is not maintained and not bersi. Likewise the existing cafeteria masi less good. The map designation of the location of the tourist attraction is good, just not the plan for the gateway in the cave. And also for facilities that aims to provide information should be held to facilitate tourist tourism activities. If the facilities are available in this beautiful tourist attraction like this ATM is already operating properly and safely. For puskesmas disekitaan beautiful tourist attraction ngalau is good for ordinary patients and patients who need first aid. If for the workshop can be summed up by a beautiful tourist attraction ngalau this is only a small workshop that can to add wind and nempel banen only. And for the accommodation available in the city payakumbuh already many just the average available sneakers are mostly three stars. And lastly for the network komuniksi available in this beautiful tourist attraction ngalau is good and good, visitors can access Android Smartphone is freely and satisfied, because the network for Android is already available with high quality that is 4G Keywords: Facilities, Condition, Management.